Gastroenterologists' preference and risk perception on the use of immunomodulators and biological therapies in elderly patients with ulcerative colitis: an international survey. Issue 8 (August 2020) - Chan, Webber; Kariyawasam, Viraj C.; Kim, Shin; Pudipeddi, Aviv V.; Paramsothy, Sudarshan; Shim, Hang Hock; Mourad, Fadi H.; Ding, Nik; Ferrante, Marc; Leong, Rupert W.
Abstract : Background and aims: Comorbidities, polypharmacy, malignancies, and infections complicate management of elderly patients with inflammatory bowel diseases (IBD). This study assessed gastroenterologists' preference in the prescription of medications or surgery to elderly patients with IBD, and the factors associated with their choices. Methods: An international case-based survey was conducted that presented three cases of steroid-dependent ulcerative colitis assessing young-age versus elderly-age patients, with and without comorbidity. Physician characteristics and practice demographics were collected. Factors associated with selection of different choices of therapy were determined by logistic regression analysis. Results: A total of 424 respondents from 41 countries were included. Vedolizumab (53.2%) and thiopurines (19.4%) were the top treatment preferences for moderate-to-severe ulcerative colitis ( P  < 0.0001). Comorbidity and older age were independently associated with more frequent use of vedolizumab ( P  < 0.0001), and less frequent use of immunomodulators and anti-tumour necrosis factor (TNF; P  < 0.0001). Comorbidity was the only independent predictor for selecting colectomy ( P  < 0.0001). A history of lymphoma (94%) and opportunistic infection (78.3%) were the most frequent conditions precluding the use of thiopurine and anti-TNF in elderly patients with IBD. Only 6.1% of respondents considered patient age a limit for vedolizumab, while 37.9% considered age as a limiting factor in prescribing thiopurines ( P  < 0.001). Geographical heterogeneity was identified with significantly more physicians from Oceania and North America favouring the use of vedolizumab. Conclusion: Vedolizumab was the preferred first-line agent in the treatment of elderly patients with IBD with steroid-dependent moderate-to-severe ulcerative colitis. Older age and presence of comorbidity influenced the selection of medication. Comorbidity was the main predictor of colectomy. Geographical heterogeneity in prescribing habits may relate to medication reimbursement in individual countries. Abstract : Supplemental Digital Content is available in the text.